2018
DOI: 10.1016/j.addbeh.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

A detailed examination of the longitudinal associations between individual and team sports and alcohol use

Abstract: This study examined the longitudinal associations between participation in individual and team sports and indicators of alcohol use during the high school years and beyond. A total of 310 youths were surveyed over six waves of data collection (ages 12, 14 to 17, and 19). Participation in individual and team sports was measured through phone interviews, whereas frequency of alcohol use, frequency of intoxication, and problematic alcohol use were self-reported. Control variables included participation in other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
4
19
0
2
Order By: Relevance
“…In this research, sport (whether individually or in a team) did not have a protective and precautionary role against the abuse of male students. This finding was in line with the results of some other studies that identified sport as a risk factor for drug abuse (smoking, alcohol) (8,32,33), but it is not accordant with research findings that found sport to be a preventive factor in smoking and drug abuse (9-13, 19, 34).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this research, sport (whether individually or in a team) did not have a protective and precautionary role against the abuse of male students. This finding was in line with the results of some other studies that identified sport as a risk factor for drug abuse (smoking, alcohol) (8,32,33), but it is not accordant with research findings that found sport to be a preventive factor in smoking and drug abuse (9-13, 19, 34).…”
Section: Discussionsupporting
confidence: 81%
“…Third, it is possible that the relationship between sport and drug abuse in males has related to other variables not investigated in this study; for example, it has been shown that abuse in athletes is influenced by their type of sports activity (33,(36)(37)(38); As the rate of tendency to smoking, alcohol and drugs in professional athletes and athletes of high schools is higher than other athletes. This finds the importance of conducting further research on the effects of various sports activities.…”
Section: Discussionmentioning
confidence: 99%
“…This research, in which we measured high levels of alcohol consumption among high-stress handball players, did not negate this claim. High levels of alcohol consumption were found among team sport athletes ( Denault and Poulin, 2018 ) along with a high level of alcohol-related disease ( Kontro et al, 2017 ). Kontro et al (2017) have found that team and combat sports have the most problems with alcohol abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Algunos estudios han mostrado como el consumo en deportistas es elevado (Denault & Poulin, 2018;Szabo, Griffiths, Aarhus Høglid, & Demetrovics, 2018). Así de este modo, en un equipo de fútbol profesional italiano se observó cómo el 66% de los jugadores eran bebedores regulares de bebidas alcohólicas (Volpi & Taioli, 2012).…”
Section: Ingesta De Alcoholunclassified